Climatic Rhythms and Prevalence of Malaria in the Municipality of Sinende in Northern Benin - GBENOU, VICTORIN VIDJANNAGNI (My University, 2023)
Malaria is endemic and the overall population in Benin is vulnerable to contracting this disease. Malaria is the leading cause of mortality in children under five and of illness for adults. It accounts for 40% of outpatient consultations and 25% of all hospital admissions. The aim of this study is to analyze the impact of climatic rhythms on the prevalence of malaria in the municipality of Sinende in northern Benin. To achieve this goal, a statistical analysis of monthly averages of climatic data, mainly rainfall, temperature and relative humidity on the one hand, and monthly and annual malaria prevalence on the other, were collected respectively at the Benin meteorological station and at the documentation centre of Sinende Bemberekè regional hospital. The data were collected over the period 2003 to 2021. The results show that the transmission of malaria is seasonal. The prevalence rate is lower in the dry season than in the rainy season. Likewise, there is a positively strong correlation (R=54%) and a coefficient of determination of (R2 = 72%) between the monthly prevalence of malaria and the monthly average rainfall. This same correlation exists between relative humidity and average monthly precipitation (R=98%). With regard to temperature, the hottest months record the highest and lowest rates of malaria cases, while the months with lower temperatures are the most malarial. The significant drop in temperature is responsible for the high prevalence of malaria cases. These results are relevant because a good control strategy should take into account the climatic conditions and the rhythm of malaria morbidity in order to combat this endemic effectively.
Keywords: Rythme climatique; prévalence; paludisme; Commune de Sinendé